Kebijakan Kriminalisasi Pengguguran Kandungan dalam Kajian Perbandingan Hukum Berbagai Negara serta Dampaknya bagi Kesehatan Ibu dan Anak (KIA) - Fanggi, Rosalind Angel (Timorese Journal of Public Health, 2020)
Indonesia is a country where religion occupies a central position and the elements must exist in the national and character building. Although has been setting in Criminal Code, but still found many cases of abortions. This paper is about to dig up how the rule of law of abortions. That there is something more profound that abortion is not only about removal of the fetus but also moral and psychological impact for youth of Indonesia. This artice aims to answer the questions: how the criminalization policy of abortion in the positive law at the future? In preparing this thesis, using a normative juridical approach, the author examines library materials is a secondary data and using the comparative law method also of the several foreign countries. The conclusion of this study is the criminalization of abortion policy set out in the positive law is not enough to guarantee protection for public health. Criminalization policy of abortion in the positive law at the future can be done by considering the arrangement of the Criminal Code abortion in some foreign as an ingredient to make legal reforms and especially considering the meaning of the precepts contained in the second sila in Pancasila. Advice can be delivered are abortions is not the best choice, but in conditions harmful should settings that give protection and health coverage of pregnant women; should have arrangements to sell the drug/vehicle used to perform abortions; about the naming of the chapter should considered using the chapter on offenses against the moral; rules should be formulated to provide legal certainty for doctors and patients: the criminalization policy of abortion settings should be based on Pancasila and national development goals.